A connection between mixing and Kac's chaos*. Issue 1 (2nd January 2019) - Androulakis, George; Musulin, Rade
ABSTRACT: The Boltzmann equation is an integro-differential equation which describes the density function of the distribution of the velocities of the molecules of dilute monoatomic gases under the assumption that the energy is only transferred via collisions between the molecules. In 1956 Kac studied the Boltzmann equation and defined a property of the density function that he called the 'Boltzmann property' which describes the behaviour of the density function at a given fixed time as the number of particles tends to infinity. The Boltzmann property has been studied extensively since then, and now it is simply called chaos, or Kac's chaos. On the other hand, in ergodic theory, chaos usually refers to the mixing properties of a dynamical system as time tends to infinity. A relationship is derived between Kac's chaos and the notion of mixing.